Critical curriculum leadership : a framework for progressive education - Ylimaki, Rose M. (New York : Routledge, 2011)
'Although traditional curriculum and instructional leadership frameworks have dominated educational administration training for almost thirty years, it has become increasingly clear that even the most recent frameworks have failed today's leaders who struggle with the politics of curriculum decisions on a daily basis. Critical Curriculum Leadership is an examination of curriculum leadership in the wake of US testing mandates and school reforms, all of which seem to support a particular set of conservative ideologies. Drawing from the author's longitudinal ethnographic study and from existing literature and research in the field, Ylimaki explores the formation of curriculum leadership in relation to broader cultural and political shifts. She shows how traditional leadership frameworks have come up short, and makes the case for an alternative leadership theory at the intersection of educational leadership and curriculum studies. She provides analytical tools that inspire progressive education and offers critical theories, strategies, research examples, problem-posing cases, and research ideas essential for curriculum leadership in the present conservative era. Critical Curriculum Leadership will appeal to the many educational leadership scholars and practitioners who are interested in developing effective and socially just curricula in their schools and districts as well as curriculum scholars who are interested in leadership issues'--
Keywords: Education -- Curricula -- United States; Educational leadership -- United States